2019
DOI: 10.1155/2019/8175803
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag-Coated SiO2@TiO2 Core-Shell Nanocomposites and Their Photocatalytic Applications towards Phenol and Methylene Blue Degradation

Abstract: Ag-coated SiO2@TiO2 (Ag-SiO2@TiO2) core-shell nanocomposites were synthesized by a two-step method, which combined hydrothermal process and photodeposition. The morphology, structure, composition, and optical properties of the Ag-coated SiO2@TiO2 nanocomposites were extensively characterized by field-emission scanning microscopy (FE-SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier-transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…This interaction may be the sharing electrons between O 2p and Fe 3d orbitals. The FeS 2 formation is demonstrated in Figure C at 161.6 and 162.8 eV, and the peak at 168.5 eV is attributable to unsaturated S atoms. , Figure D shows the Si 2p spectrum as Si–O–Si . The O 1s spectrum in Figure E indicates H 2 O and O 2 adsorbed on the FeS 2 /SiO 2 DMHS surface …”
Section: Results and Discussionmentioning
confidence: 89%
“…This interaction may be the sharing electrons between O 2p and Fe 3d orbitals. The FeS 2 formation is demonstrated in Figure C at 161.6 and 162.8 eV, and the peak at 168.5 eV is attributable to unsaturated S atoms. , Figure D shows the Si 2p spectrum as Si–O–Si . The O 1s spectrum in Figure E indicates H 2 O and O 2 adsorbed on the FeS 2 /SiO 2 DMHS surface …”
Section: Results and Discussionmentioning
confidence: 89%
“…The pore volume of the CSTNs showed the same regularity of the specific surface area, and the CSTNs of Ti/Si = 5 : 1 had the highest pore volume of 0.313 cm 2 g −1 . It can be concluded that the CSTNs with the appropriate molar ratio of Ti/Si had Journal of Nanomaterials significant effects on the samples' specific surface area, pore size, and pore geometry [35].…”
Section: Resultsmentioning
confidence: 99%
“…At present, solid microspheres can be used in profile control and flooding. The core materials of solid microspheres are SiO 2 , Fe 3 O 4 , TiO 2 , etc., which have no swelling property. The profile control and flooding effect are not good. Based on the theory of physical chemistry, polymer materials and reservoir engineering, core–shell microspheres with positive core and negative shell was synthesized by means of instrument detection, chemical analysis, and physical simulation.…”
Section: Introductionmentioning
confidence: 99%